Assessment of Health-related Quality of Life in Transfemoral Amputees: A Single Centre Cross-Sectional Study - Kamran Khan; Muhammad Alam; Waseem Javed (Indus Journal of Social Sciences, 2025)
This study explores the Dark Triad “in action” by examining how attention seeking and narcissism contribute to antisocial behavior among young adults in academic environments with the help of the Dark Triad theory. The model proposes that individuals who frequently engage in attention-seeking behaviors may possess deeper narcissistic tendencies, which ultimately translate into aggressive, manipulative, or socially disruptive behaviors. Fragile self-esteem is incorporated as a moderating variable to capture internal psychological vulnerabilities that may intensify these relationships. Data were collected from a sample of 400 students aged 18 to 24 enrolled in colleges and universities. The proposed conceptual model was tested using Smarts through Partial Least Squares Structural Equation Modeling (PLS-SEM). Overall, the study contributes to a deeper understanding of how Dark Triad traits manifest in real-life settings and offers practical implications for identifying and managing antisocial behaviors among university students.